Hispanic Immigrants' Vulnerabilities to Flood and Hurricane Hazards in Two United States Metropolitan Areas. Issue 1 (1st January 2016) - Maldonado, Alejandra; Collins, Timothy W.; Grineski, Sara E.
Abstract: Research reveals that disasters are disproportionately debilitating for marginalized social groups. Numerous studies have examined racial/ethnic dimensions of disaster vulnerability, but few have focused on Hispanic immigrants. More research on Hispanic immigrants is needed, since they constitute a major component of the Hispanic population—the largest and fastest‐growing minority group in the U.S.—and because they experience distinctive cultural and immigration status disadvantages. We examine the flood/hurricane vulnerabilities of Hispanic immigrants in comparison to U.S.–born Hispanics and non‐Hispanic whites. Using mixed methods to analyze data from 429 surveys and 31 interviews with residents living in flood zones, we examine differences in self‐protective action, risk perception, and hazard knowledge between the three groups in Houston and Miami. Hispanic immigrants exhibited lower levels of self‐protection and hazard knowledge, and higher perceptions of risk, which reflects their heightened vulnerability. Risk‐reduction programs should target the particular vulnerabilities of Hispanic immigrants, and future studies should examine their vulnerabilities in other contexts.